Latihan sebagai strategi pembangunan mampan: satu kajian kes - Muhamad, Mazanah; Teh, Saidin (Universiti Putra Malaysia Press, 1998)
Appropriate attitude, knowledge and skills are required by an individual to develop a community and sustain its development. At Perlok, a village under the Pahang Barat Integrated Agriculture Development Project such needs was effected by the government agency through various agricultural and non-agricultural related training. The local villagers welcomed such endeavor and they have participated and put what they learned into practice. They want to continue learning on matters relating to self and community development as well as farming techniques and management.